ANALISIS RASIO UNTUK MENILAI KINERJA KEUANGAN DAERAH KABUPATEN GUNUNGKIDUL TAHUN 2013-2017 - Viska Rosaliena; Zulkifli Zulkifli (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2019)
The results of the study show that the financial performance of Gunungkidul Regency which still needs attention is the regional dependency ratio and regional financial independence ratio which shows that the financial condition of the Gunungkidul Regency Government is still dominated and highly dependent on the Central Government, while on the effectiveness of Regional Original Revenue and income efficiency shows that Gunungkidul Regency has optimal and efficient capability in managing Regional Original Revenue, then the harmony ratio shows that the proportion of operating expenditure budget allocation still dominates compared to the budget for capital expenditure but there have been efforts to increase the proportion of development expenditure. This research was conducted at the Regional Financial and Asset Agency of the Gunungkidul Regency Government. This research approach uses a quantitative descriptive approach by collecting data contained in the Regional Expenditure Budget and in the Gunungkidul District Government Financial Report for the 2013-2017 budget year. The results of the study show that the financial performance of Gunungkidul Regency which still needs attention is the regional dependency ratio and regional financial independence ratio which shows that the financial condition of the Gunungkidul Regency Government is still dominated and highly dependent on the Central Government, while on the effectiveness of Regional Original Revenue and income efficiency shows that Gunungkidul Regency has optimal and efficient capability in managing Regional Original Revenue, then the harmony ratio shows that the proportion of operating expenditure budget allocation still dominates compared to the budget for capital expenditure but there have been efforts to increase the proportion of development expenditure.